Global Sequence Protocol: A Robust Abstraction for Replicated Shared State (Extended version) - Burckhardt, Sebastian; Leijen, Daan; Protzenko, Jonathan; Fahndrich, Manuel (Microsoft Research, 2015)
In the age of cloud-connected mobile devices, users want responsive apps that read and write shared data everywhere, at all times, even if network connections are slow or unavailable. The solution is to replicate data and propagate updates asynchronously. Unfortunately, such mechanisms are notoriously difficult to understand, explain, and implement. To address these challenges, we present GSP (global sequence protocol), an operational model for replicated shared data. GSP is simple and abstract enough to serve as a mental reference model, and offers fine control over the asynchronous update propagation (update transactions, strong synchronization). It abstracts the data model and thus applies both to simple key-value stores, and complex structured data. We then show how to implement GSP robustly on a client-server architecture (masking silent client crashes, server crash-recovery failures, and arbitrary network failures) and efficiently (transmitting and storing minimal information by reducing update sequences). This is an extended version of the ECOOP'15 paper.